Dampak Keberadaan Website Desa sebagai Layanan Publik dan Informasi Desa Ginolat Kecamatan Sianjur Mula-Mula Kabupaten Samosir - Welika Siboro; Dahmiri Dahmiri; Ovie Yanti (Master Manajemen, 2025)
This study aims to analyze the impact of the existence of a village website as a medium for public services and information in Ginolat Village, Sianjur Mula-Mula Subdistrict, Samosir Regency. The research employed a descriptive qualitative method with data collected through interviews, observations, and documentation. Informants were selected using purposive sampling and consisted of the village head, village officials, members of the Village Consultative Body (BPD), and community members. The results show that the Ginolat Village government does not yet have a digital information system such as a website and still relies on manual methods for delivering public services and information. As a result, residents must visit the village office in person to obtain services and access information. Therefore, this study recommends that the village government allocate funding for the development of a village website, which is expected to be a strategic solution to improve service quality, transparency, accountability, and community participation, and to support the realization of good village governance.